A Systematic Review on Ketamine and Esketamine for Treatment-Resistant Depression and Suicidality in Adolescents: A New Hope? - Simone Pardossi; Andrea Fagiolini; Simona Scheggi; Alessandro Cuomo (MDPI AG, 2024)
Treating depression in adolescents is a significant challenge, and major depressive disorder (MDD) with suicidal ideation and treatment-resistant depression (TRD) are common and potentially devastating to optimal psychological and physical development in this age group. Suicide is among the leading causes of youth mortality, and TRD occurs in up to 40% of adolescents with MDD. TRD involves severe, persistent symptoms that are hard to treat, significantly reducing functioning and quality of life. We conducted a literature search focusing on key terms related to ketamine and esketamine for MDD with suicidal ideation and TRD in adolescents, aiming to review the potential utility of these molecules in adolescents for these conditions. Ketamine has shown efficacy in reducing depressive symptoms in adolescents with TRD. Esketamine has shown efficacy in reducing depressive symptoms and treating suicidal ideation in adolescents. Both ketamine and esketamine have demonstrated favorable safety and tolerability profiles. Using these drugs for serious conditions like adolescent MDD with suicidal thoughts and TRD can effectively treat symptoms, reduce self-harm and suicide risks, and provide a window for longer-term therapeutic interventions. The prompt and effective treatment of TRD could improve adolescents' quality of life. However, more research is needed to optimize treatment protocols and evaluate long-term effects.